Licensee finance. (4th August 2014) - Stern, Peter
In this paper, presented to the "Licensing in Europe" Conference, 23–24 June 1988, London, the author looks at the special characteristics of finance for licensing and franchising. In particular, he describes the arrangements and policies of the National Westminster Bank (UK) for licensee finance, and the special requirements for retail operations.